2001
DOI: 10.1046/j.1365-313x.2001.01012.x
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for disproportionating enzyme in starch breakdown is revealed by a knock‐out mutation in Arabidopsis

Abstract: SummaryDisproportionating enzyme (D-enzyme) is a plastidial a-1,4-glucanotransferase but its role in starch metabolism is unclear. Using a reverse genetics approach we have isolated a mutant of Arabidopsis thaliana in which the gene encoding this enzyme (DPE1) is disrupted by a T-DNA insertion. While Denzyme activity is eliminated in the homozygous dpe1±1 mutant, changes in activities of other enzymes of starch metabolism are relatively small. During the diurnal cycle, the amount of leaf starch is higher in dp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
258
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(268 citation statements)
references
References 31 publications
9
258
0
1
Order By: Relevance
“…Frozen samples were homogenized and then extracted in 80% ethanol. Glc, Fru, and Suc were measured enzymatically (soluble sugars) (Guglielminetti et al, 1995a), and starch was assayed in the insoluble pellet (starch) (Critchley et al, 2001). …”
Section: Extraction and Analysis Of Carbohydratesmentioning
confidence: 99%
“…Frozen samples were homogenized and then extracted in 80% ethanol. Glc, Fru, and Suc were measured enzymatically (soluble sugars) (Guglielminetti et al, 1995a), and starch was assayed in the insoluble pellet (starch) (Critchley et al, 2001). …”
Section: Extraction and Analysis Of Carbohydratesmentioning
confidence: 99%
“…This is because analysis of an Arabidopsis dpe1 mutant demonstrated that it accumulated malto-oligosaccharides, especially malto-triose, which is its preferred substrate (Critchley et al, 2001). The amounts (Table I) and types (Fig.…”
Section: Leaves Of the Transgenic Lines Accumulate Maltosementioning
confidence: 99%
“…Mutant and transgenic plants, which lack its activity almost entirely, have been isolated (Takaha et al, 1998;Colleoni et al, 1999aColleoni et al, , 1999bCritchley et al, 2001;Wattebled et al, 2003), and based on studies on these, two contradictory proposals have been made as to its role. Following analysis of the Chlamydomonas reinhardtii sta11 mutant, it was suggested that D-enzyme is involved directly in the synthesis of the amylopectin fraction of starch (Colleoni et al, 1999a(Colleoni et al, , 1999bWattebled et al, 2003); however, no evidence for this could be found in an Arabidopsis D-enzyme mutant (dpe1; Critchley et al, 2001). It was demonstrated in this mutant that starch degradation was impaired, and it was proposed that the main role of D-enzyme is in malto-oligosaccharide metabolism during mobilization of starch in the dark period.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Four BAM isoforms of Arabidopsis are plastid localized, and three of them are involved in degradation of transient starch to maltose (Fulton et al, 2008). ISA3 (Wattebled et al, 2005;Delatte et al, 2006) is also capable of degrading transient starch to maltooligosaccharides, which are further converted either to Glc by plastidial disproportionating enzyme 1 (DPE1; Critchley et al, 2001) or by BAM to maltose. Produced maltose is metabolized to Glc in cytosol by DPE2 (Lu and Sharkey, 2004).…”
mentioning
confidence: 99%